Gross and Histological Structure of the Caudal Fin of Adult Mosquitofish , Gambusia Affinis , (Baird & Girard) - Dhahir, D.H.; AL-Mukhtar, K.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study showed that the caudal fin of adult mosquitofish (Gambusia affinis) is homocercal and rounded . It consists of 22-24 fin rays (Lepidotrichia) . Each fin ray consists of many segments . Some of these rays are short and unbranched whereas others long and branched dichotomously. Pigment cells are shown to be dispersed on the fin and they are condensened at the edges of the fin rays and at the regions of their dichotomy . Histologically the transverse section of the fin is surrounded by a fin membrane (composed of epidermis and dermis) and each fin ray consists of two semilunar hemisegments (bone –like or acellular bone) , surrounding an intrasegmental region of loose connective tissue, containing blood vessel and two bundles of nerve fibers. The transverse sections near the base of the caudal fin showed bundles of skeletal muscle fibers in company with the fin rays